1993
DOI: 10.1063/1.43200
|View full text |Cite
|
Sign up to set email alerts
|

Test facilities for evaluating nuclear thermal propulsion systems

Abstract: 505) 845-7977 MICHAEL TODOSOW BROOKHAVEN NATIONAL LABORATORY BLDG 701 UPTON, NY 11973 (516) 282-2445 ^ -S B o jj J* o i t^ B6 P e efl O *--*3» -^ ai 9 « O --60 (5 « rt 5 o fi S •a -S > ^ op ea 2 >^ •S ? -o ^ « " g <5 dp » S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Adoit;on information on the operational limits of the baseline design CSS and ETS are given in Beck et al (1993).…”
Section: Baseline Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Adoit;on information on the operational limits of the baseline design CSS and ETS are given in Beck et al (1993).…”
Section: Baseline Facilitymentioning
confidence: 99%
“…The baseline SNTP fuel element test reactor, called PIPET, is designed to support testing of high power density PBR fuel. Analysis to date of NERVA Derived fuel in several test configurations has indicated that testing within the SNTP baseline fuel test reactor is feasible (Beck et al 1993). In some configurations, the baseline SNTP ground test facility can test NERVA Derived fuel for in excess of 1 hour.…”
Section: Expanded Requirementsmentioning
confidence: 99%